2009
DOI: 10.1111/j.1365-313x.2009.03981.x
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of drought resistance by the abscisic acid receptor PYL5 through inhibition of clade A PP2Cs

Abstract: SUMMARYAbscisic acid (ABA) is a key phytohormone involved in adaption to environmental stress and regulation of plant development. Clade A protein phosphatases type 2C (PP2Cs), such as HAB1, are key negative regulators of ABA signaling in Arabidopsis. To obtain further insight into regulation of HAB1 function by ABA, we have screened for HAB1-interacting partners using a yeast two-hybrid approach. Three proteins were identified, PYL5, PYL6 and PYL8, which belong to a 14-member subfamily of the Bet v1-like supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
533
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 483 publications
(574 citation statements)
references
References 66 publications
32
533
0
9
Order By: Relevance
“…The last several years have been very fruitful in terms of elucidating the molecular mechanism of PYL-controlled PP2C activity 5,[11][12][13][14] . However, until now, no study has investigated the mechanisms underlying PP2C activity regulation at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The last several years have been very fruitful in terms of elucidating the molecular mechanism of PYL-controlled PP2C activity 5,[11][12][13][14] . However, until now, no study has investigated the mechanisms underlying PP2C activity regulation at the post-transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the binding of HAB1 by PYLs at the same ratio and in the presence of ABA turns ABA signalling on [5][6][7] . However, it has long been noticed that in the presence of ABA, PYL expression is decreased, while HAB1 and SnRK2.6 expression is greatly increased 14 . Taking the ratios of PYLs and HAB1 or HAB1 and SnRK2.6 into account, the decrease in PYLs and increases in HAB1 and SnRK2.6 under prolonged ABA treatment would promote the interaction of HAB1 and SnRK2.6 and rapidly switch ABA signalling off.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, binding of (-)ABA to the PYL5 receptor has been measured using isothermal titration calorimetry [10], although the Kd for the natural (+)enantiomer was 20-fold lower (1.1 versus 19.1 M), which indicates a higher affinity for ABA binding of the natural form. Additionally, (-)ABA promoted interaction of PYL2, PYL3 and PYL4 with HAB1 [8].…”
Section: Aba-binding Pocketmentioning
confidence: 99%
“…Finally, a chemical genetic approach using a synthetic selective ABA agonist, pyrabactin, made it possible to identify a family of soluble ABA receptors, named PYR/PYL/RCAR for PYRABACTIN RESISTANCE1/PYR1-LIKE/ REGULATORY COMPONENTS OF ABA RECEPTORS, respectively [8,9]. In a convergent approach, yeast-two hybrid screenings [9,10] and in planta interaction studies [11] identified these receptors through their capacity to bind to phosphatases type-2C (PP2Cs), which are key negative regulatory components of the pathway involved in the dephosphorylation of certain sucrose non-fermenting 1-related subfamily 2 (SnRK2) kinases [12,13,14].…”
Section: Introductionmentioning
confidence: 99%